Sala inclusiva: uma proposta didática para professores de alunos surdos e ouvintes - Lavor, Patrícia Lucena de (2022)
Research in the area of special education in the inclusive perspective, specifically, points out weaknesses in the teaching-learning process of deaf students inserted in inclusive (common) classrooms. The weaknesses that concern visuospatial communication, the Brazilian Sign Language-Libras, specific knowledge and pedagogical actions that involve deaf students are directly related to the teacher of this audience. In other words, it implies saying that accessibility needs to be expanded and understood from the subjects it is intended for. Thus, this study aims to reflect, in the context of the inclusive classroom, on the contributions of ergonomics and visuospatial communication in the teaching-learning dynamics of the deaf student, and on the importance of knowledge of these areas for teacher education. The investigation took place in two federal institutes, at the Federal Institute of Roraima - IFRR and at the Federal Institute of Amazonas - IFAM, with 19 participants, being: 08 teachers, 04 sign language translators and interpreters, 03 deaf students and 04 hearing students. The research is characterized as an intervention proposal with a public that communicates through the visual-spatial field, where the hands speak and the eyes hear and that requires, above all, from the teachers, adjustments that promote their inclusion. In this perspective, we seek to develop a qualitative investigation, based on the case study, taking as a reference the methodology proposed by Yin (2001), in dialogue Hernandéz Sampieri (2013) and Gil (2008). For the theoretical foundation, we used authors such as Quadros (2004), Gaudiot (2010), Fransolin (2016), among others, as well as we proposed to bring analyzes of the context of deaf education, research on educational practices, and also the Brazilian legislation regarding to deaf students, such as, for example, Decree nº 5.626/05 which provides for Libras. Likewise, we consulted articles, books, didactic material, dissertations and theses that dealt with the topic in question. And from this, we centered our study on the development of some operational guidelines that would help the teacher in the didactic practice, articulating it to visual aspects in the context of teaching, namely, visuospatial communication and ergonomics, in the proposition of a visual didactics. Ergonomic and accessibility issues are added to the didactic action of the teacher in the training process, whether initial or continuous. As a result, from the connection between professionals who work in the service line with deaf students, we found that the school still works with a traditional classroom organization, without considering the inclusive movement. In this sense, knowledge about ergonomics, the accessibility of visuospatial communication and visual didactics can contribute to a change in the way of conceiving the inclusive room. Thus, we understand that, in addition to contributing to the training process of teachers in inclusive classrooms, this research can also provide these teachers with an opportunity to reflect on their practice in the context of deaf education, which, therefore, will be reflected in the future school life of their students.